2017
DOI: 10.21873/anticanres.11454
|View full text |Cite
|
Sign up to set email alerts
|

KRAS Mutant Status May Be Associated with Distant Recurrence in Early-stage Rectal Cancer

Abstract: Abstract. Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…Hence, our findings confirm previous evidence that mutations at codons 12 and 13 (G13D, G12D, and G12V) of the KRAS gene are the most frequent mutations in stage I CRC [ 6 8 , 17 , 18 ], while NRAS , BRAF , and PIK3CA mutations are rare in this subgroup of CRC [ 6 8 , 17 ].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Hence, our findings confirm previous evidence that mutations at codons 12 and 13 (G13D, G12D, and G12V) of the KRAS gene are the most frequent mutations in stage I CRC [ 6 8 , 17 , 18 ], while NRAS , BRAF , and PIK3CA mutations are rare in this subgroup of CRC [ 6 8 , 17 ].…”
Section: Discussionsupporting
confidence: 91%
“…In this study, we investigated the molecular profile of a cohort of stage I CRCs and assessed its association with patient's prognosis and various clinicopathological variables. While the molecular profile of advanced CRC has been largely investigated to predict response to biological drugs [ 14 16 ], the mutational status of early CRC (stage I) has been rarely analyzed [ 6 8 , 17 , 18 ] and only in studies including stage I CRCs in heterogeneous cohorts of tumors at different pTNM stages [ 6 8 , 17 , 18 ]. Therefore, to the best of our knowledge, this represents the first study focused on the molecular profile of stage I CRC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Xiong et al ( 65 ) noticed that the KRAS status in the neoplastic lesion presented on the surface of the endometrium was different from that in the benign metaplastic areas, while Van der Putten et al ( 66 ) found that KRAS mutation appeared both in the hyperplastic lesions and the adjacent benign endometrial tissues. Other studies ( 46 , 62 ) also supported that KRAS mutation occurred in the early stages of type I EC (endometrioid) before clonal expansion, which is similar to the role of KRAS mutation in colorectal cancer ( 67 , 68 ). Endometrial atypical hyperplasia (EAH) is now believed to be the precancerous lesion of EEC, in which KRAS was also a highly mutated gene ( 63 , 64 , 69 ).…”
Section: Kras Mutations In Ec and Its Potential Value In The Fertility-spared Treatmentmentioning
confidence: 55%
“…However, the role of MGMT promoter methylation status as an early biomarker of colorectal cancer has not yet been established, despite several studies in colorectal adenoma and adenocarcinoma (14,15). In fact, Sideris et al (16) showed recently that there was no association between the status of MGMT expression and pathological features, including response to neo-adjuvant therapy. Future research will be needed to elucidate the relationship between these biomarkers and rectal cancer treatment.…”
Section: Discussionmentioning
confidence: 99%